Pengaruh Kualitas Audit, Kondisi Keuangan Perusahaan, Opini Audit Tahun Sebelumnya, dan Pertumbuhan Perusahaan terhadap Opini Audit Going Concern - Eko Budi Setyarno; Indira Januarti; . Faisal (Jurnal Akuntansi dan Bisnis, 2007)
In this study, we attempt empirically to investigate the relationship between audit quality, financial condition, previous audit report and sales growth on going concern audit opinion would receive a going concern opinion. A samples of 59 manufacturing companies listed at Jakarta Stock Exchange from 2000-2004. Logistic regression is used to examine hypothesis. The results indicate that financial condition (Altman Z-Score) and previous audit report are significantly affect the going concern audit opinion. On the other hand, audit quality and sales growth does not have effect on going concern audit opinion.